Alternative splicing in the DBD linker region of p63 modulates binding to DNA and iASPP in vitro - Rebecca Lotz; Christian Osterburg; Apirat Chaikuad; Sabrina Weber; Masato Akutsu; Anne Christin Machel; Ulrike Beyer; Jakob Gebel; Frank Löhr; Stefan Knapp; Matthias Dobbelstein; Xin Lu; et al. (Cell Death and Disease)
Abstract The transcription factor p63 is expressed in many different isoforms as a result of differential promoter use and splicing. Some of these isoforms have very specific physiological functions in the development and maintenance of epithelial tissues and surveillance of genetic integrity in oocytes. The ASPP family of proteins is involved in modulating the transcriptional activity of the p53 protein family members, including p63. In particular, iASPP plays an important role in the development and differentiation of epithelial tissues. Here we characterize the interaction of iASPP with p63 and show that it binds to the linker region between the DNA binding domain and the oligomerization domain. We further demonstrate that this binding site is removed in a splice variant of p63 where a stretch of five amino acids is replaced with a single alanine residue. This stretch contains a degenerate class II SH3 domain binding motif that is responsible for interaction with iASPP, as well as two positively charged amino acids. Moreover, the concomitant loss of the charged amino acids in the alternatively spliced version decreases the affinity of p63 to its cognate DNA element two- to threefold. mRNAs encoding full-length p63, as well as its alternatively spliced version, are present in all tissues that we investigated, albeit in differing ratios. We speculate that, through the formation of hetero-complexes of both isoforms, the affinity to DNA, as well as the interaction with iASPP, can be fine-tuned in a tissue-specific manner.